Optimization Of Internet Network Based on RSSI Analysis And Signal Coverage Simulation in the PPAI An-Nahdliyah Karangploso Environment - Abdillah, Ridho Asya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2026)
Modern Islamic boarding schools require stable internet access to support learning activities, administrative management, and communication. This study implements a Wi‑Fi network using an Orbit Star N1 module, Belden STP Cat cable, and a TP‑Link TL‑WR840N router at PPAI An‑Nahdliyah Karangploso, specifically in the Workshop Building and the Grocery Store. The implementation includes device placement planning, cable management, signal distribution optimization, and access point (AP) positioning. Performance evaluation was conducted by measuring the Received Signal Strength Indicator (RSSI) and analyzing signal coverage through simulation. The results consistently indicate that AP installation at heights of 2 m or 3 m provides the most optimal indoor Wi‑Fi coverage and signal strength. This height effectively mitigates physical obstacles and ensures more uniform signal distribution, thereby improving internet service quality to support educational, administrative, and operational activities within the boarding school environment.